Rosyjscy baptyści i ewangeliczni chrześcijanie w latach dwudziestych XX wieku - Pełczyński, Grzegorz (Przegląd Wschodnioeuropejski, 2018)
Among many religious minorities in Russia there are two important: Baptists and Evangelical Christians. Their roots are in XIX century. The unification of the groups was possible in the conditions of religious tolerance which appeared after the year 1905. The 1920s of the 20th century was the period of rich development for the Evangelical Christians as well Baptists – they constituted one million people. The fall of tsarism and later turmoils due to the Russian revolution were the reason why so many inhabitants of Russia eagerly joined the communities of Evangelical Christians and Baptists. Just the good times ends with the end of the decade.